The debate on Islamist party formation: a comparative analysis of al-Būtī and al-Qaradāwī = Perdebatan tentang pembentukan parti Islam: analisa perbandingan antara al-Buti Dan al-Qardhawi - Bachar, Bakour (International Islamic University Malaysia, 2018)
The paper examines the debate over the legal position of Islamist party formation through comparing views of two preeminent Muslim thinkers: M.S.R al-Būtī (antagonist) and Yūsuf al-Qaradāwī (protagonist). Using a text-by-text scheme, the paper tests the validity of the cited textual evidences on the basis of the primary sources of Sharī'a and the experience of today's Islamists: the Muslim Brotherhood (parent organization), Hizb al-Tahrīr, and the Justice and Development Party (AKP). Finally, the paper contends that Islamist parties are a system, accredited by Islamic principles, and a reality imposed by changing circumstances of Muslim nations in history, culture, and politics.